2006
DOI: 10.3989/scimar.2006.70n1121
|View full text |Cite
|
Sign up to set email alerts
|

Growth of common octopus (<em>Octopus vulgaris</em>) in cages suspended from rafts

Abstract: SUMMARY: Two ongrowing experiments were conducted using a raft deployed for rearing mussels during summer and winter in the Ria of Vigo, Galicia, NW Spain. Two 3 m x 1.5 m x 6 m galvanized iron ongrowing cages were suspended from this platform, each equipped with dens constructed from PVC pipe. Small common octopus (Octopus vulgaris) were captured by the small-scale creel fishery in the ria and placed in one of two sex-specific experimental cages. Specimens were fed a standard diet (fish, decapod crustacean an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 15 publications
(20 reference statements)
2
37
3
1
Order By: Relevance
“…Growth rates, close to 1% %BW/day, were similar to the ones reported for this species at Sublimi 1999, 2000;García García and Aguado 2002) and were higher than those reported by Otero et al (1999), Iglesias et al (1999Iglesias et al ( , 2000 and Chapela et al (2006), who cultured this species at lower temperatures. Temperature greatly influences cephalopod growth , food conversions (Domingues 1999) and ingestion (Domingues et al 2006(Domingues et al , 2007.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Growth rates, close to 1% %BW/day, were similar to the ones reported for this species at Sublimi 1999, 2000;García García and Aguado 2002) and were higher than those reported by Otero et al (1999), Iglesias et al (1999Iglesias et al ( , 2000 and Chapela et al (2006), who cultured this species at lower temperatures. Temperature greatly influences cephalopod growth , food conversions (Domingues 1999) and ingestion (Domingues et al 2006(Domingues et al , 2007.…”
Section: Discussionsupporting
confidence: 81%
“…Octopuses were fed frozen squid (Loligo gahi) once a day at 14:00 h, at 5% body weight per day (%BW/day). The rations should be appropriate for on-growing of this species, based on previous studies by Aguado and García García (2002), García García and Aguado (2002), and Chapela et al (2006). Food remains were collected from the tanks on the next morning and weighed previous to feeding.…”
Section: Methodsmentioning
confidence: 99%
“…Mangold (1983) reported a salinity range of 32-44 in the areas where the species is known to occur. Studies carried out in cages suspended from rafts in the Ria of Vigo, NW Spain, (Chapela et al, 2006) reported high mortalities in winter, when the salinity dropped below 29, which is below the limit of tolerance described for this species by Mangold (1983). Sobrino et al (2002) reported that heavy rainfalls caused landings of O. vulgaris to drop.…”
Section: Effects Of Culture Densitymentioning
confidence: 99%
“…Numerous studies have analyzed physiological and nutritional aspects of octopus ongrowing in tanks, but all of them used one individual per tank García and Cerezo, 2006). Other studies have evaluated factors such as stocking density using cages suspended from rafts (Chapela et al, 2006) or floating cages (Rodríguez et al, 2006).…”
Section: Effects Of Culture Densitymentioning
confidence: 99%
See 1 more Smart Citation